Plutarch's pragmatic biographies : lessons for statesmen and generals in The parallel lives - Jacobs, Susan G. (Columbia Studies in the Classical Tradition, 2017)
In Plutarch's Pragmatic Biographies , Susan Jacobs argues for a major revision in how we interpret the Parallel Lives. She integrates the existing focus on moral issues into the much broader paradigm of effective leadership found in Plutarch's Moralia. There, in addition to moral virtue, the successful leader needed good critical judgment, persuasiveness and facility in managing alliances and rivalries. The analysis of six sets of Lives shows how Plutarch carefully portrayed Greek and Roman leaders of the past assessing situations and solving problems that paralleled those faced by his politically-active audience. By linking victories and defeats to specific strategic insights and practical skills, Plutarch created "pragmatic biographies" that could instruct statesmen and generals of every era.